The Lost Journalism of Ring Lardner - Lardner, Ring, 1885-1933 (Book collections on Project MUSE., 2017)
"An anthology of journalist Ring Lardner's writings on sports and other nonfiction topics that collects works that have been mostly unavailable for decades"--